Making a Market Economy : the Institutionalizational Transformation of a Freshwater Fishery in a Chinese Community. - Wang, Ning (East Asia: History, Politics, Sociology and Culture., 2013)
First published in 2005. Routledge is an imprint of Taylor & Francis, an informa company.